2022
DOI: 10.3390/jcm11164785
|View full text |Cite
|
Sign up to set email alerts
|

Direct Anterior versus Lateral Approach for Femoral Neck Fracture: Role in COVID-19 Disease

Abstract: Background: During the COVID-19 emergency, the incidence of fragility fractures in elderly patients remained unchanged. The management of these patients requires a multidisciplinary approach. The study aimed to assess the best surgical approach to treat COVID-19 patients with femoral neck fracture undergoing hemiarthroplasty (HA), comparing direct lateral (DL) versus direct anterior approach (DAA). Methods: A single-center, observational retrospective study including 50 patients affected by COVID-19 infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Another interesting finding was made by Maccagnano et al in COVID-19 patients with femoral neck fractures treated with HA. [ 52 ] In this retrospective study of 50 patients, preservation of respiratory function was more pronounced with direct lateral CA HA in the lateral decubitus position than with DAA HA in the supine decubitus position. These findings may be similar for SuperPATH HA as this technique is also performed in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 80%
“…Another interesting finding was made by Maccagnano et al in COVID-19 patients with femoral neck fractures treated with HA. [ 52 ] In this retrospective study of 50 patients, preservation of respiratory function was more pronounced with direct lateral CA HA in the lateral decubitus position than with DAA HA in the supine decubitus position. These findings may be similar for SuperPATH HA as this technique is also performed in the lateral decubitus position.…”
Section: Discussionmentioning
confidence: 80%
“…This finding has not been previously reported in the literature. Our dataset lacked the details about surgical approach for hemiarthroplasty, however, a recent study emanating from Italy reported improved oxygenation in lateral decubitus position as compared to supine position [27].…”
Section: Discussionmentioning
confidence: 99%
“…So far (March 18), according to WHO there are 121 millions total confirmed cases and 2.68 millions deaths due to SARS-CoV-2. In Italy, on 18 March 2020, there were 3.26 millions cases of COVID-19 disease and 103,432 deaths [5][6][7].…”
Section: Introductionmentioning
confidence: 99%